The IclR-family regulator BapR controls biofilm formation in B. cenocepacia H111. - Claudio Aguilar; Nadine Schmid; Martina Lardi; Gabriella Pessi; Leo Eberl (PLoS ONE, 2014)
In Burkholderia cenocepacia H111, the large surface protein BapA plays a crucial role in the formation of highly structured communities, known as biofilms. We have recently demonstrated that quorum sensing (QS) is necessary for the maximal expression of bapA. In this study we identify BapR, a protein from the IclR family of transcriptional regulators that, in conjunction with QS, controls biofilm formation by affecting the expression of bapA. We present evidence that, in addition to bapA, BapR influences the expression of extracellular proteases, swimming motility and has a profound impact in the incidence of persister cells, making this regulator an interesting target for persister cells and biofilm eradication.